Socio-economic growth, or overcoming cost contradictions impeding the development of Russia - Shcherbakov, V. N.; Kryukova, Е. M.; Nakhratova, E. E.; Ilina, I. Y.; Potekhina, E. V.; Zotova, A. I. (Opción, 2019)
The article explores the topic of harmonious development taking into account the factors affecting the moral and psychological aspects of a perso- nality including its endogenous level. In this connection overcoming cost contradictions by means of changing value orientations is considered from the perspective of internal characteristics of motivational interests of a person as their ultimate goal. A new outlook on overcoming contradictions pertaining to the modern economic model suggests an idea of considering not only structurally connected technological relationships but also socio- economic relations reflecting the aspects of the psychology behind moral feelings and changes in value orientations in the society. Therefore, the design of control mechanisms in the economic system will be closely connected with the logic of the formation of conceptual foundations for social development.